Study on Source and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Water and Coastal Sediment from the Ngoua River in Douala, Cameroon - Ze Bilo’o Philemon; Jessie Ekoka Christelle Solange; Ngassoum Martin Benoit (Modern Advances in Geography, Environment and Earth Sciences Vol. 6, 2021)
The objective of the present study of monitoring is to point out the source and the distribution of Polycyclic Aromatic Hydrocarbons in water and coastal sediments from the Ngoua River. This paper reports the identification and quantification of 15EPA-PAHs in water and sediments samples collected from Ngoua River in Douala – Cameroon. It was then needed to evaluate by identification and quantification of the PAHs pollution in the Ngoua River. Samples of water and sediments were collected during the dry and the rainy seasons. A total of Eight (8) samples were registered with 4 samples per season per substrate. Magnetic agitation was used to extract PAHs fraction from water with hexane as a solvent. PAHs were separated by using a chromatographic column, identified and quantified by using Gas Chromatography (GC/FID). The total concentration in sediment ranged from 140.42 \(μ\)g/g to 229.47 \(μ\)g/g dry matters during the rainy season and from 48.89 \(μ\)g/g to 333.49 µg/g dry matters during the dry season. All samples showed the predominance of high Molecular Weight (HMW) PAHs due to industrial activities. At the upstream, the concentrations of PAHs were systematically lower than those found downstream indicating an influence of Nettoycam Company in the local pollution by PAHs. Principal component analysis (PCA) also showed remarkable differences of characteristics of samples collected upstream and downstream of Nettoycam Company, samples location and also of samples from rainy and dry seasons. The analyses of the extracts from water samples shows the range between 29.13 – 461.94 \(μ\)g/L is the total concentration of PAHs in the river samples. PAHs of 2 or 3 rings exhibits low concentrations and even undetectable in certain samples. Independently from the seasonal variation, PAHs with more than four rings showed the highest concentrations in the river. A predominance of petroleum sources of hydrocarbons was observed through some ratios.